Unaltered Oxytocin and Vasopressin Plasma Levels in Patients with Schizophrenia After 4 Months of Daily Treatment with Intranasal Oxytocin. (25th April 2016) - Busnelli, M.; Dagani, J.; de Girolamo, G.; Balestrieri, M.; Pini, S.; Saviotti, F.M.; Scocco, P.; Sisti, D.; Rocchi, M.; Chini, B.
Abstract : The neuropeptide oxytocin (OXT) has been proposed as a treatment for a number of neuropsychiatric disorders characterised by impaired social behaviour, including schizophrenia. Although several studies have reported the chronic administration of OXT to be safe and tolerable, its effects on circulating levels of OXT, as well as the related neuropeptide arginine vasopressin (AVP), have not been assessed. In the present study, in a within‐subjects cross‐over, double‐blind, randomised controlled trial, we assayed the plasma levels of OXT and AVP in 31 patients with schizophrenia who were treated daily for 4 months with 40 IU of intranasal OXT or placebo. Our data indicate a mean ± SD baseline OXT concentration of 1.62 ± 0.68 pg/ml, as determined by radioimmunoassay, which did not display any significant variation after chronic treatment with OXT or placebo. Similarly, the mean ± SD baseline AVP value of 2.40 ± 1.26 pg/ml remained unchanged. The present study also assessed cardiovascular and body fluid indicators (osmolality, plasma sodium concentration and systolic blood pressure), as well as a parameter for food intake (body mass index), with all observed to remain stable. By reporting that daily treatment with 40 IU of intranasal OXT or placebo for 4 months does not impact on OXT and AVP plasma levels, nor on cardiovascular, body fluids and food intake parameters, the present study represents an important step towards developing OXT as a safe treatment.